Soliton solutions for the Kundu-Eckhaus equation with the aid of unified algebraic and auxiliary equation expansion methods - Kilic, Bulent; İnç, Mustafa (Taylor & Francis Ltd, 2016)
The modified unified algebraic (MUA) and auxiliary equation expansion (AEE) methods are applied to reach the different type soliton solutions of Kundu-Eckhaus (K-E) equation. It is illustrated that MUA and AEE are very effective methods to reach the various types of the solutions of nonlinear evolution equations.
Keywords: MUA; AEE; Kundu-Eckhaus equation; soliton solutions